2020
DOI: 10.1111/jcpp.13180
|View full text |Cite
|
Sign up to set email alerts
|

The adult outcome of children referred for autism: typology and prediction from childhood

Abstract: Background: Autism Spectrum Disorder is highly heterogeneous, no more so than in the complex world of adult life. Being able to summarize that complexity and have some notion of the confidence with which we could predict outcome from childhood would be helpful for clinical practice and planning. Methods: Latent class profile analysis is applied to data from 123 participants from the Early Diagnosis Study (Lord et al., Archives of General Psychiatry, 2006, 63, 694) to summarize in a typology the multifacetted e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 31 publications
1
77
2
Order By: Relevance
“…We considered IQ and ASD symptoms, not as outcomes, but as two of several features that could be related to positive functioning. For participants at both cognitive levels, the number of outcomes met was associated with verbal IQ (within IQ-defined levels although at a small effect size), aligning with previous analyses on the same sample [Pickles et al, 2020] and past work describing the pervasive associations between verbal IQ and adaptive functioning across development [Bal et al, 2015;Liss et al, 2001], even though they are different constructs.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…We considered IQ and ASD symptoms, not as outcomes, but as two of several features that could be related to positive functioning. For participants at both cognitive levels, the number of outcomes met was associated with verbal IQ (within IQ-defined levels although at a small effect size), aligning with previous analyses on the same sample [Pickles et al, 2020] and past work describing the pervasive associations between verbal IQ and adaptive functioning across development [Bal et al, 2015;Liss et al, 2001], even though they are different constructs.…”
Section: Discussionsupporting
confidence: 83%
“…More cognitively able describes individuals with a verbal IQ of 70 or above, and less cognitively able describes individuals with a verbal IQ below 70 at the most recent assessment. These two groups have non-overlapping distributions of IQ; with means slightly above 100 for the more cognitively able and in the severe to profound range for less cognitively able adults [Pickles et al, 2020].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Follow-up studies, from childhood to adulthood, generally indicate that the severity of core autism symptoms decreases over time and many individuals show marked improvements in social and communication skills as they grow older. Among the strongest predictors of a positive outcome are the development of language and having a non-verbal IQ in or around the average range [70,71]. Within this more cognitively able group, there are a small number of adolescents or young adults who no longer meet diagnostic criteria and show no clear remaining symptoms of autism.…”
Section: Prognosis In Autismmentioning
confidence: 99%
“…Moreover, several studies have reported that at the participant level, IQ trajectories are not necessarily stable across time points (Billstedt et al 2005;Cederlund et al 2008;Farley et al 2009;Howlin et al 2004). Thus, IQ may be protective against the poorest outcome profile, but does not guarantee a good outcome (Pickles et al 2020). The mixed results may be explained by individual differences in other factors, such as level of social support (Farley et al 2009;Kobayashi et al 1992), or severity of autism symptoms.…”
Section: Introductionmentioning
confidence: 99%